A Universal Method for Preparation of Noble Metal Nanoparticle‐Decorated Transition Metal Dichalcogenide Nanobelts. (19th July 2014) - Hong, Xun; Liu, Juqing; Zheng, Bing; Huang, Xiao; Zhang, Xiao; Tan, Chaoliang; Chen, Junze; Fan, Zhanxi; Zhang, Hua
<x xml:space="preserve">Abstract</x> MoS2, TaS2, TiS2, WSe2 and TaSe2 nanobelts decorated with a PtAg alloy or Pt NPs have been successfully synthesized by etching 2D nanosheets under a mild reaction condition followed by a subsequent nanosheet‐to‐nanobelt transformation mediated by the PVP template. The PtAg‐MoS2 hybrid nanobelt coated with PVP is used as the active material in a memory device, which exhibits hysteresis behavior with the function of dynamic random access memory. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>